In vitro study on the effectiveness of gutta-percha removal between the protaper retreatment system and r-endo system in endodontic retreatment - Le, Thi Quynh Thu; Tran, Dinh Bao Duy; Le, My Huong; Nguyen, Ngoc Tam Dan (Tạp chí Y Dược Huế, 2025)
Background: During endodontic retreatment, complete removal of root canal filling material is essential for effective cleaning and disinfection of the root canal system. Various methods have been proposed for gutta-percha removal, including the rotary instruments, which is recommended because it is safe, effective, and less time-consuming. Objective: Comparison of gutta-percha removal efficiency in endodontic retreatment between the Protaper retreatment system (Dentsply Sirona) and R-Endo system (Micro Mega). Methods: The present in vitro study was conducted on 60 mandibular premolars extracted for orthodontic purposes; after initial endodontic treatment, root canal filling with gutta-percha and zinc oxide eugenol cement, the teeth were randomly divided into four groups, each group of 15 teeth. The groups were as follows: The group using the Protaper retreatment system, the group using the R-Endo system, the group using the Protaper retreatment system combined with the solvent, and the group using the R-Endo system combined with a solvent to remove gutta-percha. The time taken to remove gutta-percha was recorded. Roots were grooved into two halves, observed under a microscope, taken pictures, and evaluated with ImageJ 1.53v software, recording the amount of gutta-percha remaining on the root canal wall. Results: The study showed no significant difference in the effectiveness of gutta-percha removal between the Protaper retreatment system and the R-Endo system; all groups left gutta-percha on the canal wall. The Protaper retreatment system or R-Endo system combined with solvent left more gutta-percha on the canal wall than using only the Protaper retreatment system or R-Endo system. The amount of gutta-percha remaining on the canal wall at the cervical third, middle third, and apical third regions between the study groups did not have a statistically significant difference. The average time to remove gutta-percha showed a statistically significant difference between the study groups (p < 0.05). Conclusion: There was no difference in the efficiency of gutta-percha removal between the Protaper retreatment system and the R-Endo system in endodontic retreatment.